Mortalité de l'huître creuse C. gigas dans le Bassin de Marennes-Oléron. Résultats obtenus sur le site atelier de Ronce-Perquis en 1997-1998 - Soletchnik, Patrick; Le Moine, Olivier; Faury, Nicole; Razet, Daniel; Geairon, Philippe; Robert, Stephane; Goulletquer, Philippe (1998)
The cupped oyster, Crassostrea gigas was first introduced in France in 1967 [13]. On the Atlantic coast, the Marennes Oléron Bay (Figure 1) is the first European oyster culture basin with a cupped oyster (Crassostrea gigas) stock of 110,000 tons and an annual output of 30,000 to 40,000 tons. The Ronce oyster bank, located at the south of the bay (Figure 1), is made of 1,600 concessions spread out over 175 ha. It produces 8,000 to 10,000 tons of cupped oysters each year. In Japan, Crassostrea gigas has been cultivated for more than 1,000 years (Farley, 1992). Since the beginning of the 1960's, oyster mortality has multiplied throughout the world (Imaï et al., 1965; Sinderman, 1976; Mackin, 1961; Beattie et al, 1980). In the 60's and 70's, Japan and the west coast of the United-States were struck by summer mortality episodes destroying up to 60% of the C. gigas stocks (Glude, 1975). These mortalities are considered as the most important biological phenomenon of the first half of the 20th century (Gross et Smyth, 1946). If some mortalities are clearly identified as having a pathogenic origin (Beattie et al, 1980; Farley, 1992), others can be happen during exceptional climatic episodes (Mackin, 1961). Numerous mortality cases are often classified as of "unknown origin". L'huître creuse, Crassostrea gigas a été introduite en France en 1967 [13]. Sur la côte atlantique, le bassin de Marennes Oléron (Figure 1) est le premier bassin ostréicole européen avec un stock d'huîtres creuses (Crassostrea gigas) de 110 000 tonnes pour une production annuelle de 30 000 à 40 000 tonnes. Le banc ostréicole de Ronce, au sud du bassin (Figure 1), est formé de 1 600 concessions réparties sur 175 ha . Il produit 8 000 à 10 000 tonnes d'huîtres creuses par an. L'élevage de Crassostrea gigas est pratiqué depuis plus de 1 000 ans au Japon (Farley, 1992). Depuis le début des années 1960, des épisodes de mortalités d'huîtres se sont multipliés dans le monde (Imaï et al., 1965; Sinderman, 1976; Mackin, 1961; Beattie et al, 1980). Le Japon ...